Bolus Location Associated With Videofluoroscopic and Respirodeglutometric Events. - Perlman, Adrienne L.; He, Xuming; Barkmeier, Joseph (Journal of Speech, Language & Hearing Research, 2005)
The purpose of the present investigation was to determine the relation between specific events observed with simultaneous videofluoroscopy and respirodeglutometry. The order of occurrence was determined for each of 31 events (18 videofluoroscopic, 13 respirodeglutometric). Using 1 video frame (33.3 ms) as the maximum distance allowed between the average time’s of 2 events in the same cluster, 8 potential clusters were identified, 3 of which were statistically confirmed based on 90 Đconfidence intervals on the mean time distances between events. Confirmed clusters included the time of (a)complete velar descent and the onset of the small noninspiratory flow (SNIF), (b)full separation of the base of the tongue from the pharyngeal wall and SNIF nadir, complete upper esophageal sphincter closure, and SNIF nadir, and (c) onset of epiglottic return and apnea offset. The onset of respiratory flow occurred within 13 ms after the onset of epiglottic return. Additionally, the percentage of swallows during which the bolus head or tail was located at each of 6 locations was determined for 20 of these events (10 videofluoroscopic, 10 respirodeglutometric). The 6 locations of interest included the oral cavity, base of tongue, valleculae, pyriform sinuses, upper esophageal sphincter, and the esophagus.